探索 ：中国网络直播的“兴”与“乱” = Discuss the causes and consequences of live webcast in China - 陈磊 Chen Lei (2018)
近年来,伴随着互联网技术的日益成熟和提升，一种互动性极强的新型媒介形 式---网络直播应时而生。这种新型媒介形式不仅将媒介作为接收信息的工具, 更是将媒介作为自身日常交往的平台，改变着社会大众的工作和生活方式，让网民深陷其中，成为他们生活中不可缺少的一项休闲娱乐活动。此外，网络直播在中国也凭借着其丰富的传播内容,多元化的传播主体以及即时互动性等优势赢得许多年轻大众、商家和资本家的青睐。仿佛一夜之间, 上百家网络直播渠道就像雨后春笋般在各类网络平台兴起。因此，2016年更是被称为“中国网络直播元年”。然而，在这爆炸式增长的背后，问题也随之暴露出来，例如：低俗信息泛滥、节目同质化严重以及数据造假等，受到社会人士的关注，令人深思。本文试图探讨网络直播在中国迅速走红的缘由并结合网络直播目前存在的问题进行分析提出恰当的建议，从而促进网络直播持续健康地发展。 In recent years, along with the increasing maturity and improvement of Internet technology, a new type of media, namely live webcast has emerged. This new form of media changes the way audiences’ work and lives. In addition, its rich in content, wide range of communication subjects and real-time interactive features, has drawn numerous young people and capitalists’ attentions in China. As if overnight, hundreds of live webcast channels have sprung up in the market and nationwide-webcast is a trend. Therefore, 2016 is also known as “China’s first live webcast year”. However, behind this explosive growth, problems arise, for example, phenomenon of vulgar information flooding, serious program homogeneity and data fraud. These adverse impacts have attracted public’s concern. This article seeks to explore the reasons for the rapid popularity of live webcast in China and making appropriate recommendation to promote a sustainable and healthy development of the live webcast by analyzing the current live webcast’s existing problems.